2020
DOI: 10.1103/physreva.101.042117
|View full text |Cite
|
Sign up to set email alerts
|

Operational formulation of weak values without probe systems

Abstract: Weak values are the fundamental values for observables in a pre-and post-selected system. Weak values are typically measured by weak measurement, in which weak values appear in the change of not the pre-and post-selected system but the probe system. This indirect characteristic of weak measurement obscures the meaning of weak values for the pre-and post-selected system, in contrast to conventional physical quantities, which have a clear operational meaning. In this study, we operationally formulate weak values… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…In a similar way, the weak moment is expected to play an important role in other problems of this kind. In addition, the use of measurement methods other than the weak measurements with Gaussian probes-such as weak measurement using a qubit probe [48] and the method without a probe [49]-may find new implications for the weak moments.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way, the weak moment is expected to play an important role in other problems of this kind. In addition, the use of measurement methods other than the weak measurements with Gaussian probes-such as weak measurement using a qubit probe [48] and the method without a probe [49]-may find new implications for the weak moments.…”
Section: Discussionmentioning
confidence: 99%
“…It is straightforward to extend this scheme to an arbitrary number of operators. Note that it has also been shown that the imaginary part of a WV can be measured using a small phase shift without a probe ( 39 , 20 ). Therefore, using an approach similar to that shown here, it may be possible to apply it for an arbitrary magnitude of phase to find the sign of the imaginary parts of WVs (although this was not required for the current analysis).…”
Section: Methodsmentioning
confidence: 99%
“…In this method, the WV appears in the change of the postselection probability amplitude when a small attenuation is given between the pre- and postselections. Recently, this method has been theoretically generalized, for example, so as to be applicable to a quantum system in mixed states ( 20 ). However, the way to measure SWVs was not presented and the degree of attenuation was restricted to be weak.…”
Section: Measurement Of Swvsmentioning
confidence: 99%
“…Comparison between experiment and theory revealed that the XTAS signal was reporting the nuclear motion over the duration of the relaxation process. It is important to consider that SFI experiments could potentially exhibit electronic relaxation dynamics without considerable nuclear motion, involving highly excited Rydberg or cationic states (38,39). To prove that the observed XTAS signal dynamics solely arose from nuclear (rather than electronic) relaxation, we performed experiments and computations for the dynamics after SFI of CD 4 .…”
Section: Relaxation Dynamics Of Ch 4 +mentioning
confidence: 99%